Analisis Aplikasi Hafazan Al-quran Kanak-kanak dalam Platform Digital - Ummu Umairah binti Sapiuddin; Safinah binti Ismail; Mardhiah binti Yahaya; Nor Musliza binti Mustafa; Syarul Azman bin Shaharuddin; Khairul Syafiq bin Razali (Core Studies Center, Kolej Universiti Islam Selangor (KUIS), 2024)
Vol. 10, No. 2